Optimal control and cost-effectiveness analysis of Q-fever transmission dynamics in livestock and humans - Nkuba Nyerere; Verediana M. Mbalilo (Results in Control and Optimization)
Q-fever, caused by the zoonotic bacterium Coxiella burnetii, remains a significant global health concern due to its complex transmission dynamics involving livestock, humans, and the environment. This study develops a comprehensive mathematical model to investigate the spread of Q-fever and assess the effectiveness of five distinct control strategies targeting both human and animal populations. The model incorporates key epidemiological factors, including environmental contamination, which plays a critical role in sustaining indirect transmission. Numerical simulations and cost-effectiveness analysis reveal that early, coordinated, and sustained interventions are vital for effective disease control. In particular, the combination of livestock vaccination, gradual culling of seropositive animals, and public health education, emerged as the most cost-effective, achieving elimination in humans within two years, symptomatic livestock within three years, and asymptomatic livestock within four years. In the absence of interventions, the model predicts exponential disease spread, with Q-fever persisting for over six years in livestock and up to four years in humans, further fueled by environmental reservoirs. Across all scenarios, human infections are more quickly eliminated than those in livestock, highlighting the challenge of clearing environmental and animal reservoirs. These findings underscore the importance of integrated, long-term strategies that address direct and indirect transmission routes, combining animal health management, environmental decontamination, and public awareness to prevent endemicity and mitigate the health and economic burden of Q-fever.